KAJIAN EKSPERIMENTAL UNJUK KERJA KOLEKTOR UNTUK MESIN PENDINGIN SIKLUS ADSORPSI YANG DIGERAKKAN ENERGI MATAHARI - Purba, Jhon Sufriadi; Suhada, Khairul; Wijaya, Darma (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
The rapid development of the refrigeration system, along with the rapid advancement of technology. Adsorption refrigeration cycle is currently being developed, especially in developing countries. Adsorption refrigeration cycle is very environmentally friendly. One component of this is the generator cooling machine. Type of generator used is a flat plate. The area of ​​adsorber is 0.25 m2 with a slab thickness is 1 mm. In this adsorber filled with activated carbon as much as 8 kg. The temperature of the water will decrease with decreasing temperature refrigerant in the evaporator. On the afternoon of the desorption process occurs adsorber receives heat from the lights and the refrigerant will flow into the condenser and melt in the evaporator, at night adsorber is cooled by the outside environment resulting in the adsorption process, the refrigerant will evaporate from the evaporator into the condenser and adsorber will be absorbed. The results of this study are vacuum adsorber temperature to obtain the absorption refrigerant refrigerant methanol at 200 0C and the temperature thermostat produces 123.43 0C adsorber temperature and methanol as refrigerant absorbs 6.25 ml/kg. Keywords: Adsorption, desorption, generator, activated carbon, refrigeration